Evidence-based practice educational program in nursing students’ evidence-based practice knowledge and skills: a cluster randomized controlled trial - Cardoso, D.; Couto, F.; Cardoso, A.F.; Bobrowicz-Campos, E.; Teixeira-Santos, L.; Rodrigues, R.; Coutinho, V. (Cochrane Colloquium - Advances in Evidence Synthesis: special issue Cochrane Database of Systematic Reviews, 2020)
Background: Evidence-based practice (EBP) improves healthcare outcomes and quality. Nonetheless, there are significant gaps between research and practice which challenge use and sustainability of EBP by healthcare organizations and providers. To reduce this gap it is crucial to prepare future health professionals for EBP use in their daily care. Objectives: To measure the effect of an EBP educational program on undergraduate nursing students’ EBP knowledge and skills. Methods: A cluster randomized controlled trial was performed (ClinicalTrials.gov Identifier:NCT03411668). From the 12 optional courses of the 8th semester (fourth and final year) of the Bachelor of nursing degree, an independent researcher randomly assigned three courses to an EBP educational program and three to education as usual. The EBP educational program was carried out over 17 weeks, including 12 hours of lessons (expositive method and practice method) and six hours of mentorship to small groups of students (three sessions of two hours). The outcomes of EBP knowledge and EBP skills (as assessed by an adapted Fresno Test) were measured at baseline and after the intervention. Results: One hundred and forty-eight undergraduate nursing students with an average age of 21.95 years (standard deviation (SD) 2.25; range: 21 to 41) participated in the study. The groups were comparable at baseline regarding socio-demographic data and outcomes of interest. We found a statistically significant interaction between the intervention and time on EBP knowledge and skills (P = 0.002). From baseline to post-intervention, students’ EBP knowledge and skills improved in both groups (intervention group: P < 0.001; control group: P < 0.001). At the post-intervention, the two groups showed a statistically significant difference in EBP knowledge and skills (P = 0.011) with the intervention group having better performance than the control group. Conclusions: Both groups showed an improvement in EBP knowledge and skills from baseline to post- intervention. This result was probably due to the fact that all students receive training during the 8th semester to carry out the final year written work which is a literature review. Despite this, the undergraduate nursing students who received the EBP educational program showed higher levels of EBP knowledge and skills at completion of the program when compared with students who received only education as usual. Therefore, nurse educators could consider integrating the EBP educational program into curricula to promote EBP knowledge and skills of future nurses. Patient or healthcare consumer involvement: Eight educators from different areas (nursing, psychology, education, and physiology) participated in development of the intervention through an expert opinion process, particularly, in terms of structure, content and educational strategies. The suggestions provided by them were carefully analyzed and included in the intervention design.